Bulbar symptoms after vestibular schwannoma surgery - case report - Naděžda Lasotová; Marcela Dubová; Miloš Duba; Nikola Mišurová; Martin Smrčka (Listy klinicke logopedie, 2020)
Vestibular schwannoma is a posterior cranial fossa tumour, which is usually manifested by unilateral perceptual hearing loss, tinnitus, vertigo, facial tingling, etc. Therapy of vestibular schwannoma is chosen according to the size of tumour, its location and growth rate. Therapeutic procedures include microsurgical treatment and/or stereotactic radiosurgery and radiotherapy. Unilateral hearing loss occurs postoperatively, but bulbar syndrome may also develop through perioperative functional impairment of the peripheral nerves near the tumour site. The paper presents the role of a Clinical Speech Therapist in the diagnosis and therapy in a patient after vestibular schwannoma surgery with the development of bulbar symptoms.